Dentistry Postgraduates: User Satisfaction at the University of Costa Rica - Gutierrez-Marín, Natalia; López-Soto, Andrea (Odovtos - International Journal of Dental Sciences, 2024)
The objective of this research was to determine the level of satisfaction among patients attending the postgraduate clinics at the University of Costa Rica during 2022 using the Dental Satisfaction Questionnaire. The research included the entire population of patients and/or legal guardians who received dental care in the postgraduate clinics of pediatric dentistry and prosthodontics at the School of Dentistry between August and October 2022. A questionnaire consisting of Dental Satisfaction Questionnaire items and sociodemographic variables was applied. Descriptive statistics were performed to establish the absolute and relative frequencies, measures of central tendency, and variability, depending on the nature of the variables. The Kolmogorov-Smirnov test was used to assess the data’s conformity to a normal distribution. Questionnaire and sociodemographic variables were analyzed using the Mann-Whitney U Test and the Kruskal-Wallis Test. The response rate was 54.1%, with 95% of the participants expressing satisfaction or high satisfaction with the dental services received. Statistically significant differences were observed in some of the domains concerning sociodemographic variables: between the educational level and pain management (p=0.022) and between the frequency of dental visits and availability (p=0.008). Additionally, a statistically significant difference was observed among postgraduate categories in the domain of quality (p=0.038). This study concludes that patients attending the postgraduate clinics of prosthodontic and pediatric dentistry at the School of Dentistry, University of Costa Rica, are generally satisfied with the care they receive.